(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2008)
Summary: I. THE COMMON FINANCING SYSTEM.—II. PRINCIPLES OF THE SYSTEM.—II. HOW THE SYSTEM WORKS.—IV. TAX REVENUES OF THE AUTONOMOUS COMMUNITIES.—4.1. Autonomous Communities own taxes.—4.2. Totally ceded taxes. 4.3. Partially ceded taxes.